2016
DOI: 10.1038/srep26628
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of CYP144A1 – a cytochrome P450 enzyme expressed from alternative transcripts in Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) causes the disease tuberculosis (TB). The virulent Mtb H37Rv strain encodes 20 cytochrome P450 (CYP) enzymes, many of which are implicated in Mtb survival and pathogenicity in the human host. Bioinformatics analysis revealed that CYP144A1 is retained exclusively within the Mycobacterium genus, particularly in species causing human and animal disease. Transcriptomic annotation revealed two possible CYP144A1 start codons, leading to expression of (i) a “full-length” 434 amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…α-pinene could bind the 20 cytochrome P450 enzymes of Mycobacterium tuberculosis, involved in mycobacterial survival and pathogen in a human cell. Recently, it was reported that cyp144 and cyp130 encoded respectively by Rv1777 and Rv1256c could bind azole (Ouellet et al 2008, Chenge et al 2016, an antifungal drug that has anti-TB potent and it has been developing to be multidrug-resistant TB therapy (Gupta et al 2015). Isoamyl alcohol and furfural were showed that had interaction with alcohol dehydrogenase proteins.…”
Section: Hasil Dan Pembahasanmentioning
confidence: 99%
“…α-pinene could bind the 20 cytochrome P450 enzymes of Mycobacterium tuberculosis, involved in mycobacterial survival and pathogen in a human cell. Recently, it was reported that cyp144 and cyp130 encoded respectively by Rv1777 and Rv1256c could bind azole (Ouellet et al 2008, Chenge et al 2016, an antifungal drug that has anti-TB potent and it has been developing to be multidrug-resistant TB therapy (Gupta et al 2015). Isoamyl alcohol and furfural were showed that had interaction with alcohol dehydrogenase proteins.…”
Section: Hasil Dan Pembahasanmentioning
confidence: 99%
“…All compounds except imidazole 4, clotrimazole, and econazole 18,24 produced heterogeneous sets of low spin g-values that indicate a minimum of two different coordination states of the heme iron. The implication that ligands might acquire different binding modes with respect to the CYP144A1 heme and that there remains a proportion of enzyme in the water-coordinated resting state when it is ligand bound prompted further investigation of the enzyme's ligand binding properties using competition NMR and UV−vis experiments.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The distinct binding modes of compounds 1−3 to CYP144A1 and CYP121A1 was rationalized based on the chemical properties and steric constraints imposed by the proximal active site residues of CYP144A1 and the hydrophobicity of the CYP144A1 distal active site. 24 The ligand profile and the biophysical characteristics of CYP144A1, elucidated using these novel ligands, provide insight into the potential biological function of the enzyme. The predicted conformational flexibility and the open structure of the CYP144A1 active site, in addition to the low susceptibility of the protein to inhibition with a range of common heme binding functional groups, could indicate a role for CYP144 in xenobiotic detoxification.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a similar finding was observed when CYP125A1 was knocked out (56). More detailed analysis revealed that there are two possible start codons for CYP144A1, both of which give rise to proteins that can be expressed and purified (21). The terminal region of the longer protein appears to be disordered, but the truncated, shorter protein was amenable to crystallization and its ligand-free structure was determined.…”
Section: Cyp144mentioning
confidence: 99%